Advances in testing the effect of acceleration on time dilation using a synchrotron Mössbauer source. (24th March 2017) - Friedman, Y.; Nowik, I.; Felner, I.; Steiner, J. M.; Yudkin, E.; Livshitz, S.; Wille, H.-C.; Wortmann, G.; Chumakov, A. I.
Abstract : New results, additional techniques and know‐how acquired, developed and employed in a recent HC‐1898 experiment at the Nuclear Resonance Beamline ID18 of ESRF are presented, in the quest to explore the acceleration effect on time dilation. Abstract : New results, additional techniques and know‐how acquired, developed and employed in a recent HC‐1898 experiment at the Nuclear Resonance Beamline ID18 of ESRF are presented, in the quest to explore the acceleration effect on time dilation. Using the specially modified Synchrotron Mössbauer Source and KB‐optics together with a rotating single‐line semicircular Mössbauer absorber on the rim of a specially designed rotating disk, the aim was to measure the relative spectral shift between the spectra of two states when the acceleration of the absorber is anti‐parallel and parallel to the source. A control system was used for the first time and a method to quantify the effects of non‐random vibrations on the spectral shift was developed. For several runs where the effect of these vibrations was negligible, a stable statistically significant non‐zero relative shift was observed. This suggests the influence of acceleration on time.